Protese total fixa em função imediata confeccionada em resina composta indireta - Pivetta, Ana Claudia Real Gabrielli [UNESP]; Montandon, Andréia Affonso B. [UNESP]; Nagle, Maurício; Ricci, Weber Adad [UNESP]; Gabrielli, Marisa Aparecida Cabrini [UNESP]; Pilon, Luis Fernando (My University, 2011)
Immediate functioning of osseointegrated implants has been widely employed in edentulous patients due to its safety and high predictability. However, viability and success of immediate-loaded implants is defined by factors such as number of implants, distribution and splinting, as well as reduction of oblique loads and excessive occlusal contacts. The indirect composite resin-modified glass enable building of a highly aesthetic prosthesis, combining satisfactory resistance and better force dissipation on occlusal loading. This article describes a resin composite, mandibular fixed prosthesis on osseointegrated implants in immediate function.

Os implantes osseointegrados em função imediata estão sendo muito utilizados no tratamento reabilitador de pacientes desdentados totais por ser um procedimento seguro e de alta previsibilidade. No entanto, a viabilidade e o sucesso de tratamentos com implantes osseointegrados em função imediata são definidos por fatores como número de implantes, sua distribuição e esplintagem, redução das cargas laterais e contatos oclusais excessivos. As resinas compostas indiretas modificadas por vidro possibilitam a construção de uma prótese altamente estética, associada à resistência satisfatória e a melhor dissipação das forças durante o carregamento oclusal. Este artigo apresenta um caso de prótese total fixa mandibular implantossuportada em função imediata confeccionada em resina composta indireta.
Indirect composite, resin fixed prostheses for immediate dental implant loading
Keywords: Immediate loading; Dental prosthesis; Implant-supported prosthesis; Carga imediata; Implantes dentários; Prótese dentária fixada por implantes